2(3g+2)=6g+4

Simple and best practice solution for 2(3g+2)=6g+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3g+2)=6g+4 equation:


Simplifying
2(3g + 2) = 6g + 4

Reorder the terms:
2(2 + 3g) = 6g + 4
(2 * 2 + 3g * 2) = 6g + 4
(4 + 6g) = 6g + 4

Reorder the terms:
4 + 6g = 4 + 6g

Add '-4' to each side of the equation.
4 + -4 + 6g = 4 + -4 + 6g

Combine like terms: 4 + -4 = 0
0 + 6g = 4 + -4 + 6g
6g = 4 + -4 + 6g

Combine like terms: 4 + -4 = 0
6g = 0 + 6g
6g = 6g

Add '-6g' to each side of the equation.
6g + -6g = 6g + -6g

Combine like terms: 6g + -6g = 0
0 = 6g + -6g

Combine like terms: 6g + -6g = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| (-33)+(25)+(-24)+(26)+(-18)= | | x(x+4)-x(x+2)= | | -25v=-4 | | -2y=-12 | | (2x^2-3)+(4x)= | | 6c^2-30c+24=0 | | 2x^2+5x=18 | | 4-1+5= | | 2x+9y=66 | | 18+(x-4)2-4= | | 3x+8=2+4x | | 5x-2x+3=24 | | b^2-13b+42=0 | | 6=-31-32+9 | | -5=21w | | -30=t+3t | | (14)+(18)+(-23)+(32)= | | x+1-3=-6 | | t^2+2t-24=0 | | x+12-26+3=175 | | 4m+17=7-6m | | 7x+14-6x=-4+10 | | 20-12+y=17 | | 5x+20=x-8 | | 3X-8= | | -7-3n-4n=0 | | p+4p=10 | | -6=x-6+8x | | 4(6x-4)=8(3x+6) | | 3(y-9)=3 | | 18-15+x=10 | | 54+x=180 |

Equations solver categories